Qualitative and quantitative determination of secondary metabolites and antioxidant potential of Nymphaea nouchali flowers - Singh, Manjeet; Jain, Alok Pal (Journal of Drug Delivery and Therapeutics, 2018)
In the Indian ayurvedic system of medicine, Nymphaea nouchali is used for the treatment of diabetes, inflammation, liver disorders, cutaneous diseases, blenorrhagia, urinary disorders, menorrhagia, menstruation problem, as an aphrodisiac, bitter tonic, antimicrobial agent and anti antihepatotoxic effect. The aim of the present study is to examine Nymphaea nouchali flowers for phytochemical profile, in vitro antioxidant activities. Qualitative analysis of various phytochemical constituents and quantitative analysis of total phenolics and flavonoids were determined by the well-known test protocol available in the literature. Quantitative analysis of phenolic and flavonoids was carried out by Folins Ciocalteau reagent method and aluminium chloride method respectively. The In vitro antioxidant activity of ethanolic extract of the flowers was assessed against nitric oxide, hydrogen peroxide assay using standard protocols. Phytochemical analysis revealed the presence of phenols, flavonoids, tannins, saponins, alkaloids, fixed oil and fats. The total phenolics content of flowers ethanolic extract was (18.4 mg/100mg), followed by flavonoids (12.4mg/100mg). The activities of ethanolic flowers extract against nitric oxide and hydrogen peroxide were concentration dependent with IC50 values of 68.39 and 64.54 μg/ml respectively. The present study concluded that the crude extract of Nymphaea nouchali is a potential source of natural antioxidants and this justifies its use in folkloric medicine. Keywords: Nymphaea nouchali, Phytochemical, Antioxidant, Nitric oxide, Hydrogen peroxide, Phenols, Flavonoids